2016
DOI: 10.3171/2016.3.focus1669
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of cervical spondylotic myelopathy: an analysis of a national, administrative, longitudinal database

Abstract: OBJECTIVE The authors performed a population-based analysis of national trends, costs, and outcomes associated with cervical spondylotic myelopathy (CSM) in the United States. They assessed postoperative complications, resource utilization, and predictors of costs, in this surgically treated CSM population. METHODS MarketScan data (2006–2010) were used to retrospectively analyze the complications and cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…Prior studies have observed similar trends in surgical approaches. 2,22,28 Broadly, we found the trends seen in all cervical fusions held true for ACF and PCF. The ACF and PCF cohorts grew older and presented with a greater comorbidity burden over time, while outcomes improved and charges increased.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Prior studies have observed similar trends in surgical approaches. 2,22,28 Broadly, we found the trends seen in all cervical fusions held true for ACF and PCF. The ACF and PCF cohorts grew older and presented with a greater comorbidity burden over time, while outcomes improved and charges increased.…”
Section: Discussionmentioning
confidence: 58%
“…[3][4][5] Prior studies have assessed epidemiological trends, 6 compared the effectiveness of different surgical approaches, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and estimated the cost of the surgical management of CSM. 22,23 In 2005, an estimated 45 cervical fusions were performed per 100 000 Medicare beneficiaries, and CSM was the most common diagnosis made prior to these procedures. 2 While Wang et al quantified the rate of cervical fusions overall, it is currently unknown how national trends in cervical fusion for CSM specifically evolved over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Although this rate of complication appears high, this is consistent with the contemporary literature, with reported complication rates ranging from 16% to 41% depending on surgical approach. 32 Further, studies have demonstrated the complication rate varies significantly with age, with elderly age being associated with significantly greater complication risk. 32 , 33 Although we had no mortalities in our cohort, postoperative complications in the setting of DCM have previously been shown to increase length of stay, mortality rate, and hospitalization costs.…”
Section: Discussionmentioning
confidence: 99%
“…Bernstein et al 3 found that patients > 75 years old undergoing laminectomy or laminotomy were at higher risk of complication and mortality than younger patients. Veeravagu et al 18 found that older patients ( ≥ 65 years) had a significantly increased complication risk following ACDF and posterior fusion.…”
Section: Discussionmentioning
confidence: 99%